Ethnobotanical study of Jahangir abad, District Mardan - Ali Bahadur; Tanweer Kumar; Tahira Mushtaq; Muhammad Danish; Irfan Ullah; Fahad Nasir; Tahir Hameed; Mohib Shah; Tanweer Kumar; Muhammad Amir Zia (International Journal of Phytomedicine, 2013)
The traditional utilization of medicinal plants in healthcare performs and providing indication to new areas of research and hence its importance is now well recognized. However, information on the uses of indigenous plants for medicine is not well documented from many rural areas of Pakistan including district Mardan. The present studies were aimed to explore the ethnomedicinal profile and conservation status of threatened flora of Jahangir abad. The study area is located in the district Mardan, Khyber Pakhtunkhwa, Pakistan, contains more than 90 species directly used by local communities. Of these plants, 51 are wild plants, 23 cultivated vegetable crops and 16 are important medicinal and economically important trees. Menta longifolia, Calotropis procera, Solanum surretense, Allium sativum and Melia azedarach had multipurpose medicinal uses. Different pathological effect and pitiless collection of medicinal plants in the area has threatened the survival of some essential and valuable medicinal plants like Dalbergia sissoo and Tamarix indica in the area of Jahangir abad.